Mas̱navī yaʿnī guldastah-i maʿnī - ʿAlīẖān, Muḥammad Ḥubb (Naval Kišor, 1884)
Long narrative poem in rhyming couplets (mas̲navī) about the significance in an Indian branch of the Qadiri Sufi order (the followers of Shāh Ābādānī Siyālkūṭī, 1738-1805) of carrying a black handkerchief and the secrets behind this act